The investigation of NaTi2(PO4)3@C/Ag as a high-performance anode material for aqueous rechargeable sodium-ion batteries. (August 2018) - Yao, Xiaolin; Luo, Yanxiang; Li, Yue; Li, Wanwan; Fang, Minhua; Shui, Miao; Shu, Jie; Ren, Yuanlong
Graphical abstract: Highlights: Facile preparation of NaTi2 (PO4 )3 @C/Ag. An extraordinary self-rejuvenation process was observed every other 20–30 cycles. Retain a capacity of 71.7 mA h g −1 even at 5 C after 200 cycles. Abstract: Silver and carbon coated NaTi2 (PO4 )3 is synthesized via a facile sol-gel method, with polyvinyl alcohol as carbon source and silver nitrate as Ag source. NaTi2 (PO4 )3 @C/Ag is characterized by XRD, SEM, TEM, EDS and XPS. It can be found that C/Ag composite layer is uniformly coated on the surface of NaTi2 (PO4 )3 . Compared with the pure NaTi2 (PO4 )3, NaTi2 (PO4 )3 @C/Ag material demonstrates significantly higher rate capability and cycling stability. It can deliver an initial discharge capacity of 126.5 mA h g −1 at a current rate of 2 C with the capacity retention of 94.5% after 100 cycles. It can still deliver an initial discharge capacity of 97.5 mA h g −1 at a current rate of 5 C with a substantial capacity retention of 83.8% after 400 cycles. It is worth mentioning that NaTi2 (PO4 )3 @C/Ag also exhibits pretty good rate capacity. When the current density ranges from 1 C, 2 C, 5 C, 10 C and finally back to 1 C, NaTi2 (PO4 )3 @C/Ag electrode still retains a discharge capacity of 84.6 mAh g −1 after 200 cycles at 5 C corresponding to a capacity retention ratio of 83.5%.